(untitled) (Global Journal of Science Frontier Research, 2016)
Designing to make use of the climatic conditions of the site has always been a challenge; especially when buildings are to be naturally ventilated. The current study examines how effective orientation is as a parameter for the reduction of cooling loads in multi-storey office buildings. The approach is experimental in nature where a case-study building was selected and a parametric simulation with T as the software was applied. The results indicated among others that whiles the annual cooling load for the actual orientation is 288.43kWh.m².a¹; there is an 11.81kWh.m².a¹ reduction when the orientation is 270° away from the actual of 0°. Again, in terms of cooling loads per unit floor areas, the 270° angle performed better. This indicates that if attention is paid to orientation and aspect ratio as parameters during the design of a structure, it would go a long way in ensuring that the design behaves sustainably. It is recommended that the orientation along the north and south axis should be adhered to as it aids in the free flow of natural ventilation through the indoor spaces.